Synopsis of the genus Bothriochloa (Poaceae: Andropogoneae) in India - Landge, Shahid Nawaz; Shinde, Rajendra D. (Phytotaxa, 2021)
During the taxonomic study of the genus Bothriochloa from India, B. ewartiana was reported for the first time in Asia from India. Earlier, it was known only from Australia, Lesser Sunda Island (Sumbawa, Timor), Philippines (Luzon), and Papua New Guinea (Madang). We have discussed about its amphitropical disjunct distribution over a vast continental gap with respect to some variability reported in the morphological attributes. A hypothesis behind its seclusion from Far East is also discussed. The images of the habitat and habit of B. ewartiana along with its detailed comparison with a close species B. woodrovii are provided. The taxonomic limits of each Indian species of Bothriochloa along with their ranges of morphological variations and distribution have been discussed in a detail. The Indian endemic B. parameswaranii (synonym nova) has been relegated, based on the morphological study, as a new taxonomic synonym of B. insculpta. Moreover, keys to identify closely allied genera and the species of Bothriochloa in India are provided. At the end, identification, taxonomic notes and the range of variations of Dichanthium foulkesii, D. jainii & D. concanense have been discussed in a detail.